Mountain Ecosystems as Natural Laboratories for Climate Change Experiments - Tito, Richard; Vasconcelos, Heraldo L.; Feeley, Kenneth J. (Frontiers in Forests and Global Change, 2020)
Experimental studies are needed to empirically examine the effects of climate change on terrestrial organisms and to serve as the basis for predictions and management practices. As such, designing and implementing experimental systems that can simulate complex changes in the natural environment is currently a major area of interest of climate change science. Most climate change experiments (e.g., infrared heaters, open-top chambers) are typically performed within small, controlled environments and often manipulate just temperature and/or CO2 concentration. Other factors are more difficult to control (e.g., wind speed, soil moisture) or are ignored (e.g., biotic interactions), leading to uncertainties in the results and limiting our ability to make realistic predictions about species’ responses. We examined the natural variation of abiotic and biotic factors along mountain elevational gradients in order to highlight the potential for using these systems as natural laboratories for climate change research and experiments. The high variability of different abiotic and biotic factors along elevational gradients provides a good opportunity to carry out field transplant/translocation experiments aimed at answering some critical questions, including: How will new biotic assemblages affect key interactions and processes? What are the factors that influence species assemblages under novel climates? How do local abiotic factors influence the establishment of species migrating into novel and climatically suitable habitats? Based on empirical evidence, we strongly encourage researchers to take advantage of the natural environmental gradients found in mountains to study the potential direct and indirect impacts of climate change on species, communities and biodiversity as a whole.